Dependence of quartz wettability on fluid density. Issue 8 (28th April 2016) - Al‐Yaseri, Ahmed Zarzor; Roshan, Hamid; Lebedev, Maxim; Barifcani, Ahmed; Iglauer, Stefan
Abstract: Wettability is one of the most important parameters in multiphase flow through porous rocks. However, experimental measurements or theoretical predictions are difficult and open to large uncertainty. In this work we demonstrate that gas densities (which are much simpler to determine than wettability and typically well known) correlate remarkably well with wettability. This insight can significantly improve wettability predictions, thus derisking subsurface operations (e.g., CO2 geostorage or hydrocarbon recovery), and significantly enhance fundamental understanding of natural geological processes. Key Points: Rock wettability strongly correlates with gas density Water wettability decreases with increasing gas density Wettability depends on gas density (and not gas type)